Bilingual intercultural education: a direct experience with the amazonic thought cocama-cocamilla in the native community "independencia" -río amazonas-Loreto. - Hagiwara Grández, Ferdinand Luis (2019)
The purpose of this article is, to reflect on some important aspects of Bilingual Intercultural Education, based on a research experience of the cocama-cocamilla Amazonian thought, in the native community "Independencia" Río Amazonas-Loreto during 2014, which will allow us to address some concepts such as ancestral knowledge, interculturality, Amazonian Thinking cocama-cocamilla, hidden curriculum in the educational activity of the “Independencia” community.